Talent Management and Workers’ Commitment: Oil & Gas Firms in Nigeria - Edeh Ogbu Friday; Mlanga Sunday (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose: This investigates the relationship between talent management and workers’ commitment to oil and gas firms in Nigeria using a cross-sectional survey. Ten oil and gas servicing firms were surveyed using simple random sampling. Design/Methodology: A population of 125 managers and supervisors were surveyed from ten oil and gas firms in Rivers state while a sample of 95 was ascertained from the population using Krejcie and Morgan sample size determination table. Reliability of the instrument was determined using Cronbach Alpha. Face and content validity was employed. 95 copies of the questionnaire were administered to managers and supervisors but 74 copies were correctly filled and returned. Pearson Product Moment Correlation Coefficient (rs) was used to analyze the hypotheses with the aid of statistical package for social sciences (SPSS 20.0) while respondents’ characteristics were analyzed using frequency distribution. Findings: The study found that talent management has a positive significant relationship with workers commitment. It concluded that talent management measured in terms of talent attraction, talent development and talent retention promotes workers commitment in oil and gas firms in Nigeria. Practical Implications: This study recommends that managers of oil and gas firms should endeavor to employ all compensation plans necessary to retain talents in the industry as this will enhance their commitment towards achieving organizational goals.